2013
DOI: 10.1080/09540105.2013.837031
|View full text |Cite|
|
Sign up to set email alerts
|

A survey of Aflatoxin M1 in some commercial milk samples and infant formula milk samples in Goa, India

Abstract: A survey of aflatoxin M1 (AFM1) contamination in packaged milk and infant formula milk samples in the Goan market, India, was conducted using high performance liquid chromatography, association of analytical communities approved commercial kit and a sensitive chemiluminescent sandwich enzyme-linked immunosorbent assay (ELISA). A total of 72 samples of infant formula milk food (18) and packaged milk samples (54) was analysed. One hundred per cent of the analysed samples exceeded the European Communities recomme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Higher levels of AFM 1 in animal milk samples from Pakistan are also reported by Ismail et al (2016) , according to which 93% out of a total of 520 milk samples were found positive for AFM 1 , while 53% samples were reported exceeding the EU maximum limit for AFM 1 in milk (0.05 μg/L). Kanungo and Bhand (2015) reported the level of AFM 1 in IFM samples from India and found that all samples had AFM 1 above the maximum EU limits. The range of AFM 1 in IFM samples was 0.501-0.713 μg/kg.…”
Section: Resultsmentioning
confidence: 99%
“…Higher levels of AFM 1 in animal milk samples from Pakistan are also reported by Ismail et al (2016) , according to which 93% out of a total of 520 milk samples were found positive for AFM 1 , while 53% samples were reported exceeding the EU maximum limit for AFM 1 in milk (0.05 μg/L). Kanungo and Bhand (2015) reported the level of AFM 1 in IFM samples from India and found that all samples had AFM 1 above the maximum EU limits. The range of AFM 1 in IFM samples was 0.501-0.713 μg/kg.…”
Section: Resultsmentioning
confidence: 99%
“…AFM 1 levels in a high percentage of samples were found to exceed the limit of 50 ng/kg set in the EU, and many samples crossed the 10-fold higher limit permitted in other regions of the world. In particular, the high AFM 1 levels detected in infant formula in two studies in India [ 30 , 32 ] and in sweets in Pakistan [ 42 ] raise concerns. Thus, as these products are consumed by vulnerable parts of the population, they should be included in future sampling plans for AFM 1 analysis in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Akhtar et al [21] determined the AFM 1 presence in infant formulae in Pakistan, evaluating 13 samples, in which 53.84% of the samples were positive to the toxin presence and 30.76% exceeded the EU limit. Kanungo and Bhand [22] evaluated the AFM 1 presence in infant formulae in India, determining that in 72 evaluated samples, all of them were above the EU permitted limit (25 ng/kg) and 75% of the samples exceeded the USA and Indian Food regulation limit (500 ng/kg). Er et al [4] published a study evaluating the AFM 1 presence in infant formula in Turkey, evaluating 84 samples with only one sample positive for the toxin.…”
Section: Occurrence Of Afm 1 In Infant Formulaementioning
confidence: 99%